Age- and sex-specific effects of maternal separation on the acoustic startle reflex in rats: early baseline enhancement in females and blunted response to ambiguous threat - Granata, Lauren; Parakoyi, Abigail; Brenhouse, Heather C. (Frontiers in Behavioral Neuroscience, 2022)
Early life adversity increases the incidence of later-life anxiety disorders. Dysregulated threat processing, including responsivity to ambiguous threats, is an indicator of anxiety disorders and can be influenced by childhood experiences. The acoustic startle response is a defensive reflex displayed by mammals when exposed to sudden intense stimuli reflecting individual variations in vigilance. These measures can be altered by previous experience and experimental modifications, including the introduction of unconditioned aversive stimuli. Rats emit ultrasonic vocalizations (USVs) in the 22kHz range in negative contexts. As such, 22kHz USVs are an ethologically relevant social cue of environmental threat shown to induce anxiety-like behavior in recipient rats. Because the timing of symptom manifestation after early life adversity can differ between sexes, the current study sought to identify the age- and sex-specific effects of daily maternal separation (MS) on responsivity to ambiguous threat in rats. In Experiment 1, rat pups underwent MS or control rearing from postnatal day (P)2-20, then underwent behavioral testing beginning on P24, 34, or 54 to determine whether MS modified the baseline startle response or the modulation of startle by 22kHz USVs. In Experiment 2, rats were tested in a light-enhanced startle paradigm at P54 after MS or control rearing to determine whether MS influenced light-enhanced startle. Results show an enhancement of the baseline startle magnitude by MS in females at P34. At P54, MS reduced the modulation of the startle response by 22kHz USVs and prevented light-enhanced startle, indicating an MS-induced deficit in defensive responsivity when exposed to potential threat.